Effective Post-Disaster Reconstruction of Infrastructure : Experiences from Aceh and Nias - MDF-JRF Secretariat (World Bank, Jakarta, 2014)
The Multi Donor Fund for Aceh and Nias (MDF) and the Java Reconstruction Fund (JRF) have played significant roles in the remarkable recovery of Aceh, Nias and Java, following some of the worst disasters in Indonesia in recent years. The MDF and the JRF, which is patterned after it, are each considered a highly successful model for post-disaster reconstruction. This paper discusses the value of a phased approach to post-disaster reconstruction as a successful means to manage short-term expectations while delivering long-lasting, results of high quality. The natural disasters of late 2004 and early 2005 left a trail of human loss and destruction in Aceh and Nias. There was huge pressure on all actors involved in the reconstruction process to act fast and get projects ready for implementation. The MDF adopted a phased approach to the reconstruction. The implementation of nearly all projects in the roads sub-sector was fully satisfactory, with positive economic benefits attributable to the various projects. Most of the projects under the MDF infrastructure portfolio placed significant emphasis on capacity building to enhance the sustainability of assets created. The MDF's experience in implementing its large-scale infrastructure program offers many lessons for future reconstruction efforts in similar contexts in Indonesia elsewhere.